Performing Interpersonal Violence Court, Curse, and Comedy in Fourth-Century BCE Athens - Riess, Werner (De Gruyter, 2012)
This book offers the first attempt at understanding interpersonal violence in ancient Athens. While the archaic desire for revenge persisted into the classical period, it was channeled by the civil discourse of the democracy. Forensic speeches, curse tablets, and comedy display a remarkable openness regarding the definition of violence. But in daily life, Athenians had to draw the line between acceptable and unacceptable behavior. They did so by enacting a discourse on violence in the performance of these genres, during which complex negotiations about the legitimacy of violence took place. Since discourse and reality were intertwined and the discourse was ritualized, actual violence might also have been partly ritualized. By still respecting the on-going desire to harm one's enemy, this partial ritualization of violence helped restrain violence and thus contributed to Athens' relative stability.